Development of subgrade layer using scrap tire and stabilised expansive soil. (2021) - Kavinkumar, V.; Elavarasan, S.; Anandaraj, S.; Dharmaraj, R.
Abstract: For every country its development purely lies upon its own Infrastructure development. The roads that bring the connectivity across the country are a very important objective in that aspect. The quality and stability of subgrade are some of the major factors responsible for adequate performance and service of the road during its lifespan. The foremost complications faced by the highway engineers is the instability of subgrade. In India we have wide distribution of Black Cotton Soil, which brings major drawback and provide high level of difficulty in designing and laying roads over it. Maximum percentage of wastes are in the form of solid wastes e.g. waste tyres, broken glasses, spent nuclear fuels, plastics etc. 33 million vehicles have been added to Indian roads in the last three years; one can only visualize the number of tyres that will be discarded. Tyre shreds induce low horizontal stresses since they are lightweight and have relatively high shear strength. Customizing of tyre shreds for civil engineering application has numerous benefits.